Antimicrobial release from a lipid bilayer titanium implant coating is triggered by Staphylococcus aureus alpha-haemolysin - Thomas Wilkinson (Applied Surface Science, 2024)
Infections represent a significant challenge in joint replacements, often leading to the need for high-risk revision surgeries. There is an unmet need for novel technologies that are triggered by pathogens to prevent long-term joint replacement infections. The use of supported lipid bilayers (SLBs) with encapsulated antimicrobial agents, which are responsive to bacterial virulence factors, offers an exciting approach to achieving this goal. In this study, Ti was functionalised using octadecylphosphonic acid (ODPA) to form an SLB with an encapsulated antibiotic (novobiocin), effective against methicillin-resistant Staphylococcus aureus. Using the solvent-assisted method, the SLB with encapsulated novobiocin was developed on the surface of ODPA-modified Ti quartz crystal microbalance (QCM) sensors. QCM monitoring and fluorescence microscopy supported the successful formation of a planar SLB with encapsulated novobiocin. Incorporation of novobiocin in the SLB resulted in significantly reduced attachment and viability of S. aureus NCTC 7791, with no significant reduction in human bone marrow stromal cell viability. Additionally, in the presence of varying concentrations of α-haemolysin, a virulence factor from S. aureus, the SLB demonstrated a dose-dependent release pattern. The findings indicate the possibility of creating a biocompatible implant coating that releases an antimicrobial in the presence of a bacterial virulence factor, in a dose-dependent manner.